Recombinant Mycobacterium paragordonae Expressing SARS-CoV-2 Receptor-Binding Domain as a Vaccine Candidate Against SARS-CoV-2 Infections - Kim, Byoung-Jun; Jeong, Hyein; Seo, Hyejun; Lee, Mi-Hyun; Shin, Hyun Mu; Kim, Bum-Joon (Frontiers in Immunology, 2021)
At present, concerns that the recent global emergence of SARS-CoV-2 variants could compromise the current vaccines have been raised, highlighting the urgent demand for new vaccines capable of eliciting T cell-mediated immune responses, as well as B cell-mediated neutralizing antibody production. In this study, we developed a novel recombinant Mycobacterium paragordonae expressing the SARS-CoV-2 receptor-binding domain (RBD) (rMpg-RBD-7) that is capable of eliciting RBD-specific immune responses in vaccinated mice. The potential use of rMpg-RBD-7 as a vaccine for SARS-CoV-2 infections was evaluated in in vivo mouse models of two different modules, one for single-dose vaccination and the other for two-dose vaccination. In a single-dose vaccination model, we found that live rMpg-RBD versus a heat-killed strain could exert an enhanced cell-mediated immune (CMI) response, as well as a humoral immune response capable of neutralizing the RBD and ACE2 interaction. In a two-dose vaccination model, live rMpg-RBD in a two-dose vaccination could also exert a stronger CMI and humoral immune response to neutralize SARS-CoV-2 infections in pseudoviral or live virus infection systems, compared to single dose vaccinations of rMpg-RBD or two-dose RBD protein immunization. In conclusion, our data showed that live rMpg-RBD can lead to an enhanced CMI response and humoral immune responses in mice vaccinated with both single- or two-dose vaccination, highlighting its feasibility as a novel vaccine candidate for SARS-CoV-2. To the best of our knowledge, this study is the first in which mycobacteria is used as a delivery system for a SARS-CoV-2 vaccine.